Distance interventions for enhancing preparedness in informal caregivers of older adults: A systematic review protocol. - Fernanda L F Dal Pizzol; Kathleen F Hunter; Jennifer Baumbusch; Hannah M O'Rourke (PLoS ONE)
Introduction Informal caregivers provide care to older adults but report lack of preparedness to enact the role. Intervention programs delivered by distance offer one alternative to support preparedness. Three review studies conducted to date have highlighted the benefits of distance interventions for enhancing preparedness among informal caregivers of older adults. However, these reviews have been limited in presenting and discussing how intervention components influenced outcomes. Additionally, they have not compared different distance delivery approaches for informal caregivers of older adults or assessed their varying impact on preparedness outcomes. These limitations make the effectiveness of diverse distance approaches unclear. Aim To evaluate the effects of distance interventions aimed at enhancing preparedness among informal caregivers of older adults. Methods This protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) guidelines and is guided by the Cochrane Handbook for Systematic Reviews of Interventions. It has been registered in PROSPERO (CRD42023400668). Databases used in the search will include CINAHL, Cochrane Library, EMBASE, MEDLINE, PsycINFO, Scopus, and ProQuest Theses and Dissertations Global. The search will not be restricted by publication year to include all relevant studies. Studies published in English and Portuguese will be included. Study quality will be assessed using Downs and Black's checklist. If metanalysis is possible, it will be performed using the ReviewManager (RevMan) software. Conclusions The study will be the first of its type to systematically review and synthesize components and approaches of distance interventions aimed at supporting preparedness of informal caregivers of older adults.